Islamic Banks’ Stability: Full-Fledged vs Islamic Windows - Arief Ichwanul Hasan; Tastaftiyan Risfandy (Journal of Accounting and Investment, 2021)
Research aims: This paper investigates whether Islamic windows have better stability than full-fledged Islamic banks.Design/Methodology/Approach: A sample of 14 Islamic banks and 19 Islamic windows banks in Indonesia from 2013 to 2018 was used in this study. Both ordinary least squares and panel fixed effects were employed to examine the stability of both Islamic banks’ types.Research findings: Our empirical result suggested that full-fledged Islamic banks were less stable than their Islamic windows counterparts. This result remained consistent after running the model with different estimators and conducting various robustness tests.Theoretical contribution/Originality: Our result implies that Islamic windows could enjoy their market position to maintain stability without converting themselves into full-fledged Islamic banks because the Islamic banking market's current condition is highly competitive.Practitioner/Policy implication: Our empirical evidence supports the Indonesian governments' policy in converting Islamic windows banks into full-fledged Islamic banks if the market's competitive condition is well monitored by the regulators.Research limitation/Implication: This research result is limited only to the Indonesian setting and can be different if the analysis is taken using a sample from other countries.